Fast alternating direction implicit method for efficient transient thermal simulation of integrated circuits - Heh, Ding Yu (2020)
This paper presents fast alternating direction implicit (FADI) method for efficient transient thermal simulation of integrated circuits. The FADI method is formulated from Peaceman-Rachford's ADI and Douglas-Gunn's ADI methods. The update procedure of the proposed method has basic implicit form that features derivative-free right-hand side and hence, better efficiency and conciseness. Subsequently, through the basic implicit form of FADI method, the relationship between classical Peaceman-Rachford's and Douglas-Gunn's ADI methods can be clarified and elucidated in detail. A unified boundary condition that can cater to common kinds of boundary conditions in thermal simulation is also introduced. To further accelerate FADI method, the graphics processing unit is also utilized through Compute Unified Device Architecture implementation. It is shown that high efficiency gain can be achieved using the proposed FADI method through large time step size and data parallelism, while maintaining stability and good accuracy. As numerical illustration, an integrated circuit structure with microchannel cooling is demonstrated. Numerical results further ascertain the cooling effect of the microchannels.